From corn to popcorn? Urbanization and food consumption in sub-Sahara Africa : Evidence from rural-urban migrants in Tanzania - Lara Cockx; Liesbeth Colen; Joachim De Weerdt (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
There is rising concern that the ongoing wave of urbanization will have profound effects on eating patterns and increase the risk of nutrition-related non-communicable diseases. Yet, our understanding of urbanization as a driver of food consumption remains limited and primarily based upon research designs that fail to disentangle the effect of living in an urban environment from other socioeconomic disparities. Data from the Tanzania National Panel Survey, which tracked out-migrating respondents, allow us to compare individuals' dietary patterns before and after they relocated from rural to urban areas and assess whether those changes differ from household members who stayed behind or moved to a different rural area. We find that individuals who relocated to urban areas experience a much more pronounced shift away from the consumption of traditional staples, and towards more high-sugar, conveniently consumed and prepared foods. Contrary to what is often claimed in the literature, living in an urban environment is not found to contribute positively to the intake of protein-rich foods, nor to diet diversity. Though we do not find a strong association with weight gain, these changes in eating patterns represent a clear nutritional concern regarding the potential longer-term impacts of urbanization. Our results however also indicate that the growth of unhealthy food consumption with urbanization is largely linked to rising incomes. As such, health concerns over diets can be expected to spread rapidly to less-urbanized areas as well, as soon as income growth takes off there. Our findings clearly call for more in-depth research that may help to improve health and food and nutrition security as well as correctly predict food demand and adapt trade, agricultural and development policies.
Keywords: 330